ПЕДАГОГІЧНІ УМОВИ ПІДГОТОВКИ ПРОФЕСІЙНО КОМПЕТЕНТНОГО ПЕДАГОГА ПРОФЕСІЙНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2008)
In the article an author describe the problem of propation competent teacher of the vocational training for the professional educational system.